2021
DOI: 10.3389/fonc.2021.660955
|View full text |Cite
|
Sign up to set email alerts
|

FLVCR1 Predicts Poor Prognosis and Promotes Malignant Phenotype in Esophageal Squamous Cell Carcinoma via Upregulating CSE1L

Abstract: ObjectiveDysregulation of feline leukemia virus subgroup C receptor 1(FLVCR1) expression has been investigated in several tumors. However, the expression and role of FLVCR1 in esophageal squamous cell carcinoma (ESCC) remain largely unknown.MethodsFLVCR1 expression in tissues was measured by immunohistochemical staining (IHC). Celigo assay, MTT assay, colony formation, caspase 3/7 activity analysis, wound healing assay, Transwell migration, and invasion assay were applied to assess the effects of FLVCR1 on ESC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…10 FLVCR1 knockdown inhibited cell proliferation and induced cell apoptosis. 11 Mutations of the FLVCR1 gene are related to neurodegenerative diseases, and the common symptoms are posterior column ataxia and retinitis pigmentosa. 5,9,[12][13][14][15][16] Most studies indicated patients had absent reflexes, a typical feature of peripheral nerve involvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 FLVCR1 knockdown inhibited cell proliferation and induced cell apoptosis. 11 Mutations of the FLVCR1 gene are related to neurodegenerative diseases, and the common symptoms are posterior column ataxia and retinitis pigmentosa. 5,9,[12][13][14][15][16] Most studies indicated patients had absent reflexes, a typical feature of peripheral nerve involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of the FLVCR1 reduce heme export activity, enhance oxidative stress, and increase sensitivity to programmed cell death 10 . FLVCR1 knockdown inhibited cell proliferation and induced cell apoptosis 11 …”
Section: Introductionmentioning
confidence: 99%